Relationship between white matter changes and aggression in methamphetamine dependence - Lederer, Katharina Johanna (Department of Psychiatry and Mental Health, 2015)
Background: Methamphetamine (MA) abuse is a growing problem in the world and especially in South Africa’s Western Cape. Amphetamine-type stimulants have become the second most widely abused illicit drugs worldwide. Admission data from substance abuse treatment centres in the Western Cape show the fastest increase for any drug ever noted in the country in MA related admissions. MA has neurotoxic effects on the brain leading, amongst other effects, to white matter (WM) changes. Moreover, increased levels of aggression are commonly found in individuals with MA abuse. Although behavioural deficits are well described, the underlying mechanisms are still poorly understood. While previous studies have examined WM abnormalities relating to cognitive impairment, none have investigated associations between WM integrity in individuals with MA dependence and aggression. Methods: Diffusion Tensor Imaging (DTI) was used to investigate WM changes in 40 individuals with MA dependence and 40 matched healthy control subjects. Aggression was measured with the Buss & Perry Questionnaire in 40 MA users and 36 controls. Two approaches to assess WM integrity in the brain were employed. First, whole brain voxel wise comparison across subjects using tract based spatial statistics (TBSS) in FSL was used. Fractional anisotropy (FA), mean diffusivity (MD), parallel diffusivity (λ║) and perpendicular diffusivity (λ┴) were compared between the two groups. Second, a region of interest (ROI) approach was used, which focused on three WM tracts in the frontal brain, commonly found to play a role in aggressive behaviour: (1) the genu of the corpus callosum (CC), (2) the cingulum and (3) the uncinate fasciculus.